Fruits and vegetables, as a source of nutritional compounds and phytochemicals: Changes in bioactive compounds during lactic fermentation. (February 2018) - Septembre-Malaterre, Axelle; Remize, Fabienne; Poucheret, Patrick
Abstract: Nutritional recommendations emphasize fruit and vegetable consumption. This is related to health-benefits associated with bioactive nutritive molecules (nutrients, vitamins, minerals, fibers, …) as well as non-nutritive phytochemicals (phenolic compounds, flavonoids, bioactive peptides, …) content of these types of foods. Fermented fruit or vegetable products are part of various diets worldwide. Lactic acid bacteria (LAB) fermentation is common among the various fermentation processes used. It produces changes in both profile and types of bioactive compounds. Molecules such as bioactive peptides, short chain fatty acids or polysaccharides are generated while sugar content or anti-nutritional compounds are decreased and phenolic compounds are converted to molecules with added biological value. These transformations, associated with prebiotic and/or probiotic potential supply as well as improvement of food components bioaccessibility and bioavailability, result in modifications of health-related properties. Lastly, interactions between ingested fermented food, intestinal microbiota and their correlations to metabolomics profiles and health represent an important perspective deserving to be further explored. Graphical abstract: Image 1 Highlights: Fruits and vegetables are rich in nutrients and phytochemicals of interest such as polyphenols. Lactic fermentation is an ancestral process of food preservation but with a renew interest. Fermentation increases the level of health beneficial compounds and hydrolyses anti-nutrients. Fermented plant products could contribute to good health benefits.